Analisa Pengaruh Faktor-Faktor Yang Menyebabkan Nasabah Perbankan Konvensional Beralih Ke Perbankan Syariah - Cut Delsie Hasrina; Lukman T.Ibrahim; Sarah Amelia Br Ginting (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This study aims to analyze and empirically prove the influence religiosity, knowledge, level of service, margin level on the behavior of conventional banking customers who switch to sharia banking. The subjects of this study are sharia bank customers who switch from conventional banking to sharia banking. The object of this study is the number of bank sharia in Banda Aceh. The sample of this study are 170 respondents were selected using purposive sampling method. The analysis used in this study is multiple linear regression analysis using SPSS 24.0. Based on the analysis that has been done, it is obtained that religiosity and knowledge do not affect the behavior of conventional banking customers to switch to sharia banking. Meanwhile, the company's services and margin levels proved to have a positive and significant effect.